Artificial Intelligence in Education: Enhancing Learning Experiences through Personalized Adaptation - Christopher Davis; Tony Bush; Stephen Wood (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2024)
This research delves deeply into the transformative potential that artificial intelligence holds within the realm of education, shedding light on its capacity to revolutionize the learning paradigm by uncovering previously unexplored avenues. However, it underscores the imperative for a comprehensive, well-informed, and discerning approach towards the development and implementation of AI technologies in educational settings, recognizing the multifaceted nature of the challenges at hand. Through diligent research endeavors and a nuanced comprehension of the ramifications of AI advancements, it is envisaged that we can harness its advantages to the fullest extent while mitigating potential risks and adverse effects. Consequently, artificial intelligence is poised to emerge as an invaluable tool in fostering a more adaptable, efficient, and inclusive educational landscape, fostering the cultivation of an environment that champions openness and diversity, and fortifying the learning capabilities of all students, thereby paving the way for a more equitable and enriched learning experience.